In Vitro Comparative Analysis of Fall Armyworm (Spodoptera frugiperda) Development: Evaluating Natural versus Artificial Diets - Talib, Asma; Fazlullah; Joshi, Ravindra Chandra; Sheikh, Umer Ayyaz Aslam Sheikh (Malaysian Applied Biology, 2025)
The fall armyworm (Spodoptera frugiperda) is a notorious invasive pest of global economic concern, impacting a diverse array of crops, with a significant preference for maize. Its swift dispersal and capacity to adapt to various environments present substantial obstacles to consistent crop yields and global food supplies. This research sought to evaluate the growth and developmental characteristics of S. frugiperda larvae provided with either a natural diet (maize leaves) or a specifically formulated artificial diet, maintained under controlled laboratory conditions (25 ± 1 °C; 65 ± 5% relative humidity). Egg masses were collected and the resulting larvae were raised on two feeding regimens, each repeated three times: (i) a natural diet consisting of maize foliage, and (ii) an artificial diet with a precisely defined composition of carbohydrates, proteins, lipids, vitamins, minerals, antimicrobial substances, and binding agents. Larvae that consumed the artificial diet displayed notably faster development, improved survival, greater pupal development, and less microbial contamination in comparison to those raised on maize leaves. The stable nutritional content of the artificial diet promoted more consistent and predictable growth, while the natural diet resulted in increased variability, likely due to changes in the nutrient content of plant tissues. These results emphasize the utility of artificial diets in enabling large-scale, uniform rearing of S. frugiperda for various experimental purposes, particularly investigations into insect toxicology and biological control approaches.